Agglomeration within urban areas: evidence from Brazil - SILVA, Rubens Lopes Pereira da (2017)
The research provides an analysis of the agglomeration levels of the economic activities of the Metropolitan Region of Recife in the years of 2006 and 2011 using distance-based measures. In analyzing industries of both manufacturing and services in an intra-urban context, our research expands a literature that, in Brazil, has focused on Manufacturing and regional differences. We estimate the concentrations applying the " metric proposed by Duranton and Overman (2005). Classical measures, such as Gini or E-G index, are biased with respect to the size of the study areas. The ", being a measure based on distances, does not suffer from this bias and can be tested by statistical inference. We show that the region has a remarkable level of agglomeration: 57% and 56% of the sectors are concentrated for 2006 and 2011, respectively (68% and 71% in strict samples); results that are compatible with similar work for other countries. of the 20 most agglomerated sectors, 15 and 16 (2006 and 2011) are services. Endorsing previous research, we find that activities related to computing, law, accounting, architecture and engineering show a tendency towards localization. Three general conclusions can be extracted from the work 1) in both years, there are many more localized groups than dispersed ones; 2) there is not much difference in terms of share of localized and dispersed industries between years; 3) the tendency towards localization is fainter when firms are weighted by workforce.